2001
DOI: 10.1021/es001805+
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of PAH, PCB, and Pesticide Concentrations in Air at Two Rural Sites on Lake Superior

Abstract: Atmospheric concentrations of polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and pesticides were compared at Brule River and Eagle Harbor, two rural sites on Lake Superior that are part of the Integrated Atmospheric Deposition Network (IADN). Brule River lies 40 km southwest of Duluth, MN, a small industrial city, and Eagle Harbor is in Michigan's upper peninsula, 400 km east of Brule River. Pesticide and PCB concentrations were similar at both sites. Day-by-day regression analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
61
3
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 29 publications
(42 reference statements)
9
61
3
1
Order By: Relevance
“…Similar gas-phase ΣPCB concentrations have been reported for the urban area of Integrated Atmospheric Deposition network (IADN) station, Chicago, as 1800 ± 170 pg m − 3 (Buehler et al, 2001). Tasdemir et al (2005) have reported that the average ΣPCB concentration in Chicago was 1900 ± 1700 pg m − 3 .…”
Section: Ambient Air Concentrationssupporting
confidence: 68%
“…Similar gas-phase ΣPCB concentrations have been reported for the urban area of Integrated Atmospheric Deposition network (IADN) station, Chicago, as 1800 ± 170 pg m − 3 (Buehler et al, 2001). Tasdemir et al (2005) have reported that the average ΣPCB concentration in Chicago was 1900 ± 1700 pg m − 3 .…”
Section: Ambient Air Concentrationssupporting
confidence: 68%
“…In fact, detailed analyses indicated that the PAH concentrations were especially elevated at Sturgeon Point when the winds blew from Buffalo (17 ). We can infer from these findings that Buffalo is a source of PCBs and PAHs at the Sturgeon Point location.…”
Section: Spatial Trendsmentioning
confidence: 81%
“…Representative mass spectra of gem-dialkylalkanes in bitumen of sample M2: (a) 3-ethyl-3-methylpentacosane, C 28 H 58 ; (b) 3,3-diethyltricosane, C 27 H 56 ; (c) 5,5-diethyltricosane, C 27 H 56 ; and (d) 6,6-diethyltetracosane, C 28 H 58 (Simoneit, Lein, Peresypkin, Osipov, 2004; reproduced with permission, Elsevier Science Publishers, copyright 2004). & Wakeham, Schaffner, & Giger, 1980a,b), and branched into fate and accumulation of synthetic compounds such as pesticides/ herbicides in the food chain (Simonich & Hites, 1995a,b;Baker & Hites, 1997;Hillery, Basu, & Hites, 1997;Buehler, Basu, & Hites, 2001). Currently, the concerns are with risk assessment, human health effects, and bioactive compounds as endocrine disruptors (DeCaprio, 1997;Hanselman, Graetz, & Wilkie, 2003;McArdell et al, 2003;Sexton, Needham, & Pirkle, 2004).…”
Section: B Environmental Chemistrymentioning
confidence: 99%